2015
DOI: 10.7326/m14-1189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Amount and Intensity on Abdominal Obesity and Glucose Tolerance in Obese Adults

Abstract: Fixed amounts of exercise independent of exercise intensity resulted in similar reductions in abdominal obesity. Reduction in 2-hour glucose level was restricted to high-intensity exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
129
1
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(150 citation statements)
references
References 23 publications
9
129
1
11
Order By: Relevance
“…In nonThal populations, regular physical activity has been shown to decrease depression and improve mood 7 , school performance 8,9,10 , glucose tolerance 11,12,13 , weight maintenance 14 , body composition 15 and bone health 16,17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…In nonThal populations, regular physical activity has been shown to decrease depression and improve mood 7 , school performance 8,9,10 , glucose tolerance 11,12,13 , weight maintenance 14 , body composition 15 and bone health 16,17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…The pedometer is commonly used in everyday life, even with apps for smartphones, and it is possible to experience that monitoring one's daily physical activity induces a spontaneous increase of physical activity. Studies that compared amounts and intensity of exercise in different combinations in previously inactive men concluded that the results are similar in terms of reducing body weight [36], ameliorating insulin sensitivity, cardiorespiratory fitness, and skeletal muscle mitochondrial content [37]. In particular, brief (10 min) sessions of relatively intense exercise induced the same effects as more prolonged (30 min) sessions of moderate-intensity continuous training.…”
Section: How Much Physical Activity Is Needed To Produce Biological Cmentioning
confidence: 71%
“…Adherence was reported as about 2,000 kcal/week and about 3,800 kcal/week, respectively [13]. Project FINE also included glucose tolerance tests, as did two other RCTs [11,13,19]. With these tests, dose effects were observed in FINE [13] and in a four-armed, 24-week trial of men and women by Ross et al [11] in which the highest dose group, averaging 168 min/week aerobic exercise (40.0 min/session × 4.2 days/week) at 75% VO 2max experienced the greatest reduction in 2-h glucose.…”
Section: Discussionmentioning
confidence: 99%
“…2016;6(2): [35][36][37][38][39][40][41][42][43][44][45] effects would inform cancer prevention guidelines. Such trials have been conducted and measured insulin resistance indicators [11][12][13][14][15][16][17][18][19]; however, they were limited for informing postmenopausal breast cancer prevention because they were small [12][13][14], tested lower-intensity exercise [14,15,19] or shorter durations of exercise that may be suboptimal for cancer prevention [15,16], or they did not focus on postmenopausal women [11,13,17].…”
Section: Introductionmentioning
confidence: 99%